Avgust Pavel: Prekmurska Slovenska Slovnica. Vend Nyelvtan: Maribor: Filozofska fakulteta, Mednarodna založba Oddelka za slovanske jezike in književnosti (Zora; 100). 474 str. - Šek Mertük, Polonca (Slavia Centralis, 2020)
The article presents the Slovene translation of the first scientific grammar of the Prekmurje language Prekmurje Slovene grammar of August Pavle.
Keywords: Slovenian language; Prekmurje standard language; history of language; grammar; review